(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract The research aims to verify the dimensions of tax justice that exist in Iraq, and to determine their impact on tax compliance. Through a revised model of tax justice based on the literature of tax justice according to the classification of the studies of (Saad, 2009), (Wenzel, 2002), by using a questionnaire as an experimental measurement tool designed to be in line with perceptions of tax justice in Iraq. To define the dimensions of tax justice (the independent variable) with eight dimensions (Distributive justice, Exchange justice, Vertical justice, Horizontal justice, Retributive justice, procedural justice, administrative justice) and measure its impact on tax compliance (the dependent variable). The number of distributed questionnaires was (49). Distributed to a number of professionals and academics in the field of specialization. A set of statistical methods were used to study the relationship between the two research variables, using the statistical program (SPSS) to analyze the data and calculate (the arithmetic mean, correlation coefficient, coefficient of variation, F test, R2 coefficient of determination, T test, Cronbach’s alpha coefficient). The results of the research showed that there is a relationship and a positive effect of significant significance between tax justice and tax compliance. And that the most influential dimensions of tax justice in tax compliance were the exchange justice dimension and the distributive justice dimension, while the least influential dimensions in tax compliance came personal justice dimension. The research recommended using the proposed model of tax justice perceptions presented in this study, by financial policy makers, to create a fairer tax system that enables taxpayers and the General Tax Authority to establish a more effective system, to enhance the level of tax compliance.